The relationship between the employees’ perceptions of Corporate Social Responsibility, Work Engagement and Human Values - Anabela Pereira; Duarte, A.; Trindade, G. (III Symposium on Ethics and Social Responsibility Research, 2015)
In a business context, it is clear the reciprocal influence established between employees engaged in the performance of the organization and the effects of certain practices and policies adopted by the company in employees’ attitudes and behaviors. This research focuses on possible relationships between the employees’ perceptions of corporate social responsibility (CSR), the work engagement and human values. Our study is inspired in the European perspective of CSR (European Commission, 2001) and in the Cohen’s approach (2010). The work Engagement dimensions were identified following the perspective of Schaufeli and Bakker (2003). For the human values the Schwartz’ model (1999) was applied. Thus, the three psychometric instruments are the Scale of Social Responsibility (Vicente, Rebelo and Inverno, 2011), the Utrecht Work Engagement Scale and the Portrait Values Questionnaire (PQV-21) of Schwartz. The questionnaire was applied to a sample of 257 employees. The main results suggest that some of the human values explain negatively the identified dimensions of employees’ perception of CSR as well as the work Engagement dimensions. It is also concluded that work Engagement is positively explained by the CSR perceptions in the Marketplace and Workplace dimensions; however, these CSR dimensions act as mediators between age and work Engagement.